On the poverty–growth elasticity - Arndt, Channing; Mahrt, Kristi; Schimanski, Caroline (United Nations University, 2017)
Poverty–growth elasticities are frequently calculated to provide insight into the inclusiveness of the growth process. Mathematically, the formula employed to calculate the growth elasticity of poverty leads to lower values for higher initial poverty rates, ceteris paribus. This paper discusses the potential for this property to produce misleading results both over time and space. Poverty–growth semi-elasticities provide a more robust measure of the responsiveness of poverty to growth.